19.1k views
5 votes
Which of these equations have no solution? Check all that apply.

2(x + 2) + 2 = 2(x + 3) + 1
2x + 3(x + 5) = 5(x – 3)
4(x + 3) = x + 12
4 – (2x + 5) = (–4x – 2)
5(x + 4) – x = 4(x + 5) – 1

2 Answers

4 votes

Answer:

1, 2, and 5

Explanation:

User Et
by
6.0k points
2 votes

Answer: 2(x + 2) + 2 = 2(x + 3) + 1

Steps:

2x + 6 = 2x + 7

Subtract 6 from both sides

2x + 6 - 6 = 2x + 7 - 6

Simplify

2x = 2x + 1

Subtract 2x from both sides

2x - 2x = 2x + 1 - 2x

Simplify

0 = 1

The sides are not equal.

NO SOLUTION

User Souames
by
6.0k points